2003
DOI: 10.1901/jeab.2003.79-351
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Schedules: Reinforcer Magnitude Effects

Abstract: Five pigeons were trained on pairs of concurrent variable-interval schedules in a switching-key procedure. The arranged overall rate of reinforcement was constant in all conditions, and the reinforcermagnitude ratios obtained from the two alternatives were varied over five levels. Each condition remained in effect for 65 sessions and the last 50 sessions of data from each condition were analyzed. At a molar level of analysis, preference was described well by a version of the generalized matching law, consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
50
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 26 publications
14
50
1
Order By: Relevance
“…They found that each food delivery shifted local preference toward the alternative from which it came, and the largest amount of food (four pellets) shifted local preference more than the smallest amount of food (one pellet). This result differed from that of Landon et al’s () showing similar effects of small and large amounts of food on local preference. To address the question of whether or not shifts in local preference depend on relative or absolute amount of food, Aparicio and Baum () compared preference shifts following large (four pellets) and small amounts (one pellet) of food with those of an earlier study in which one pellet was delivered at both alternatives (Aparicio & Baum, ).…”
contrasting
confidence: 99%
“…They found that each food delivery shifted local preference toward the alternative from which it came, and the largest amount of food (four pellets) shifted local preference more than the smallest amount of food (one pellet). This result differed from that of Landon et al’s () showing similar effects of small and large amounts of food on local preference. To address the question of whether or not shifts in local preference depend on relative or absolute amount of food, Aparicio and Baum () compared preference shifts following large (four pellets) and small amounts (one pellet) of food with those of an earlier study in which one pellet was delivered at both alternatives (Aparicio & Baum, ).…”
contrasting
confidence: 99%
“…To illustrate, consider that, in matching analyses of basketball shot selection, preference has been defined in terms of the relative frequency of two‐point versus three‐point shot attempts. In laboratory matching experiments, unequal reinforcement magnitudes create bias (e.g., Landon, Davison, & Elliffe, 2003). By analogy, a three‐point shooting bias is expected in basketball, and has in fact been widely observed (e.g., Alferink et al, 2009; Hitt, Alferink, Critchfield, & Wagman, 2007; Romanowich et al, 2007; Vollmer & Bourret, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Questions also may be raised about whether behavior allocation matches the relative ratio of reinforcement magnitudes. A small body of reports indicates that for nonhumans it does (e.g., Davison & Baum, 2003; Elliffe, Davison, & Landon, 2008; Grace, 1995, 1999; Kyonka & Grace, 2008; Landon et al, 2003; Lau & Glimcher, 2005). For human subjects, the few available studies show limited matching to reinforcer magnitude (Dube & McIlvane, 2002; Sanders, 1968; Schmitt, 1974; Wurster & Griffiths, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Even in these situations, a variety of animals choose larger amounts of foods when given choices between discrete sets of identical food items (e.g., Addessi, Crescimbene, & Visalberghi, 2008; Anderson, Awazu, & Fujita, 2000; Anderson et al, 2005; Beran, 2001; Call, 2000; Hanus & Call, 2007; Rumbaugh, Savage-Rumbaugh, & Hegel, 1987; Uller, Jaeger, Guidry, & Martin, 2003) and continuous quantities such as liquids (e.g., Suda & Call, 2005; vanMarle, Aw, McCrink, & Santos, 2006; Wood, Hauser, Glynn, & Barner, 2008). Extensive research has shown that magnitude of food reward guides choice behavior in a variety of contexts even when other variables such as delay length to reward and unpredictability of reward also are manipulated (e.g., Green, Myerson, Holt, Slevin, & Estle, 2004; Landon, Davidson, & Elliffe, 2003; MacDonall, 2008; Steinhauer, 1984; Young, 1981). …”
mentioning
confidence: 99%